Розрахунок зонної структури та її параметрів для 2D індій моноселеніду - Tuziak, O.Ya.; Dziuba, V.I.; Galiy, P.V.; Nenchuk, T.N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2025)
InSe as a 2D structure possesses carrier mobility and adaptive band gap at the level of the best nanoelectronic materials. Structurally the crystal is layered — it contains monolayers, each consisting of four monoatomic sheets in the sequence Se-In-In-Se and due to the weak interlayer connection different arrangments of monolayers are possible, namely crystals with ?, ? and ? polytypes. Theoretical calculations of the band structure for three polytypes of 2D-InSe were performed using density functional theory with the generalized gradient approximation in the Perdew–Burke–Ernzerhof parameterization. Crystal structure data for the calculations were taken from experiments and refined by relaxation. Spin–orbit interaction was not considered. The following band characteristics for each of the considered polytypes (namely ?, ? and ?-2D-InSe) were obtained: band gap width, density of states, and effective carrier masses. It was concluded that the band gaps were typically underestimated by DFT, so one can’t prove InSe band gap decrease with increase in the number of monolayers, predicted in some works, for any of the polytype. Due to the lowest among the studied polytypes carrier effective mass (namely electron) 2D-?-InSe exhibits the highest carrier mobility and the lowest density of states and this conclusion does not contradict the available for today data. It was also underlined that for experimental study it is crucial to distinguish between different polytypes of 2D-InSe samples as their energy band structure for different polytypes vary. Some discrepancies and potential directions for further research are outlined.